A análise do aspecto jurídico e temporal do homicídio passional - Valles, Jacqueline do Prado (2011)
The homicide is one of the most horrific crimes that a man can commit, since that it is the elimination of a being of it s own kind, but particularly in this work, were addressed the driving factors of what is called passionate murder , that which is practiced by the criminal under extreme emotional influence, that can be, love, hate, anger or fear. Feelings that cannot be ignored during the verification process of the crime and the imposition of criminal liability. The forensic psychiatric explains that the emotions felt by the criminal at the moment of the crime can the considered so severe, to the pint of exclusion of the guilt of the agent, not allowing him the perception of the criminal act, It s not the case of the passionate murder provided under the article 121 § 1º last part of the Criminal Code, in this case, the criminal acts with the domain of violent emotion, after unjust provocation by the victim . Such emotional state is so engaging that prevails all the rational feeling of the agent, and under this circumstance so psychologically dominating, that it becomes essentially difficult to impose a predefined time lapse , between the victim attitude and the criminal reaction, at the crime moment